Perioperative Myocardial Damage and Heart Failure in Noncardiac Surgery. Part 2. Reduction of the Risk of Perioperative Cardiac Complications by Pharmacological Measures and Optimization of Anesthetic and Critical Care Support (Review) - I. A. Kozlov; A. M. Ovezov; E. L. Petrovskaya (Общая реаниматология)
The second part of the overview presents and analyzes the current data on the methods of adjuvant pharmacological cardioprotection and possibilities of optimizing the anesthetic support and perioperative monitoring in high cardiac risk patients. Amendments made in international guidelines for the last 2–3 years on the basis of conclusive studies and meta-analyses have been examined. Cardioprotection mechanisms and information about its implementation in real clinical practice have been analysed. It has been shown that by no means all drugs under discussion can be widely used for prophytlactic purposes. Contemporary evidencebased recommendations concerning the optimization of anesthetic support and perioperative monitoring are given. A conclusion has been made that practical implementation of a comprehensive strategy aimed at reduction of the risk of cardiac complications might ensure decrease of both the incidence of severe cardiac complications and mortality due to them.